(untitled) (Tempo e Argumento, 2021)
Since the year 2000, inspired by the struggle of the organization “Abuelas de Plaza de Mayo”, other organizations of people seeking their origins begin to emerge in Argentina. Form the beginning these organizations received women who were looking for their stolen children, stating that they were presumed dead, that nobody “never showed them the body” or that they never received a death certificate. One or those women is Rosa, who was born in 1954 and at the age of fourteen had a son in a midwife´s clandestine clinic in the province of Buenos Aires. Rosa claims that she “stole it” and was a key witness in the trial where three women managed to sentence that midwife to twelve years in prison for having sold them at birth. In this article, trough in-deph interviews with Rosa and other women in the same situation, and ethnographic records of the midwife trial, I aim to understand, on the hand, the senses of justice, motherhood and abandonment present in these women´s, and on the other, the configuration of these stolen children demands in the field of justice. In this way, through the discourses built around these women and their pregnancies which, in their majority, threatened the legitimate ways of conceiving family and kinship, I try give account of the historical experience of these women intersected by class, gender and age and the ways in which these experiences are currently resignified.. Keywords: Maternidad; Robo de niños; Mujeres; Justicia; Argentina.